Ekaristi sebagai Kurban dalam Pemikiran Joseph Ratzinger - Eka Novi Setyanta, Oktavianus (Jurnal Teologi (Journal of Theology), 2019)
In this era, culture of hatred and degradation of love among others have grown and this becomes our big concerns. In this situation, Church presents as the concrete image of Gods love for the world. In the Apostolic Exhortation Sacramentum Caritatis, J. Ratzinger, as Holy Father Benedict XVI, emphasize that Eucharist as the sacrament of charity must be social in character (S. Car. 89). The foundation of social characteristic of this sacramental mysticism is Gods love seen in Jesus Christs sacrifice as the victim of the cross. Church of Semarang Archdiocese tries bring face of Gods love in the midst of the world through Rencana Induk Keuskupan Agung Semarang (RIKAS) 2016-2035. By the writer, the ideas of J. Ratzinger are connected to the implementation of culture of love as seen in RIKAS 2016-2035 about the mission to create the culture of love. This culture finds its sources and powers in the Eucharist as the sacrament of charity. Through celebration of Eucharist, people are united with Christ by means of sacramental mysticism. In the light of Ratzingers theology of sacrifice, mystical unity with Christ refers to the unity to the Gods love (John 15:13). Love, in its nature, always has character of going outside from itself through self-offering. That is why sacramental mystical unity in Eucharist always have social characteristic, which means that this requires real actions in the world. This social characteristic of Eucharist is showed in the efforts of building the culture of love, so it is clear that Eucharist becomes the source of culture of love.